1996
DOI: 10.1177/026921559601000305
|View full text |Cite
|
Sign up to set email alerts
|

Functional assessment of urinary incontinence: the perineal pad test

Abstract: Perineal pad tests are simple, noninvasive functional tests which have been recommended for the evaluation of patients with urinary incontinence. Most are based on the one-hour pad test introduced by Sutherst and co-workers and standardized by the International Continence Society. The major problem with the one-hour pad test is its lack of sensitivity. Therefore a stringent test procedure was developed, whereby the limit of patient tolerance was reached. Mean end volumes of 568 ml (648 ml) immediately after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…2) The pad test adopted was not sensitive enough to detect a change in severity of incontinence [23][24][25] or had poor compliance, whilst the frequency/volume chart had extremely poor compliance (only half the sample returned both pre and post frequency/volume charts). This last problem was not highlighted by the initial review that was conducted to determine the most suitable duration for a frequency/volume chart 26 (although more recent studies have reported similar findings 27 ).…”
Section: Changes In Strength and Endurancementioning
confidence: 99%
See 1 more Smart Citation
“…2) The pad test adopted was not sensitive enough to detect a change in severity of incontinence [23][24][25] or had poor compliance, whilst the frequency/volume chart had extremely poor compliance (only half the sample returned both pre and post frequency/volume charts). This last problem was not highlighted by the initial review that was conducted to determine the most suitable duration for a frequency/volume chart 26 (although more recent studies have reported similar findings 27 ).…”
Section: Changes In Strength and Endurancementioning
confidence: 99%
“…However, it should be noted that although the one-hour pad test allowed standardization due to the use of a pre-defined protocol, this may have been at the expense of sensitivity. [22][23][24] A recent study 25 reported that although reliable, the ICS-recommended onehour pad test underestimated patients' incontinence. However, in this study the opposite was found.…”
Section: Changes In Severity Of Incontinencementioning
confidence: 99%